Affimer sandwich probes for stable and robust lateral flow assaying - Goyal, Garima (2022)
Lateral flow assays (LFAs) widely deployed for on-site diagnosis have predominantly utilized antibodies as recognition molecules. Antibodies with limited thermal stability deteriorate the performance of the LFA over time. Herein, we demonstrate a stable and robust LFA by utilizing thermally stable peptide-based 12-14 kDa affimers as recognition molecules, in lieu of conventional protein-based antibodies to analyze complex samples with a significantly improved shelf life at room temperature. The model system studied here is that of interleukin-8 (IL8) biomarker for validating the efficacy of the proposed approach, using a pair of affimer probes that demonstrates dual functionality of capturing and reporting. Affimers immobilized on the test zone of LFA serve as capture probes for IL8-affimer-MB complexes. Whereas affimers conjugated with the MBs that enable extraction of IL8 from the sample matrix serve as reporters for visual detection. The MB complexes captured at the test zone resulted in brownish test bands that enable concentration-dependent detection of IL8. The assay yielded sensitive visual detection of IL8 at ng/mL levels (~ 0.1 ng/mL and 1 ng/mL in buffer and human plasma, respectively), within 20 min, using sample volumes of ~ 100 µL. Importantly, the stability of affimer-incorporated LFA improved significantly in contrast to antibody-incorporated LFA over time, even when stored at 4 °C. Therefore, the proposed affimer-based LFA in conjunction with MBs offer stable and reliable detection of biomarkers at clinically relevant concentration ranges in complicated matrices, even without requiring cold storage, hence, offering a promising avenue for on-site diagnosis in resource-limited settings.